Functional Impressions in Complete Denture and Overdenture Treatment - Hrvoje Kršek; Nikša Dulčić (University of Zagreb. School of Dental Medicine, 2015)
Tooth loss can cause loss of occlusal, masticatory, esthetic, physiognomic, phonetic and psychosocial function of patients. The most frequently used treatment method of completely edentulous patients and patients with a small number of remaining teeth are complete dentures or overdentures. One of the most important clinical and laboratory procedures in their fabrication is functional impression taking. The aim of this paper was to present procedures of taking functional impressions in fabrication of complete dentures and overdentures, using standardized techniques and materials. An accurate functional impression together with other correctly performed clinical and laboratory procedures ensure good retention and stability of dentures, which is a precondition for restoring patients' lost functions.